Comparison of the Effectiveness of Electrical Energy Production from Livestock Manure by Optimization using Combined Heat and Power (CHP) Method: A Literature Review - Ilham, Wahyu Ilham Kholiq; Arwan Suryadi Pramanta; Jalaludin Rumi; Ahmad Dzaky Harahap (Universitas Negeri Semarang, 2024)
Livestock manure is a potential source of renewable energy. This study compares the effectiveness of electrical energy production from livestock manure with and without optimization using the Combined Heat and Power (CHP) method. Using the CHP method can improve energy efficiency by utilizing the heat generated from burning livestock manure to produce electricity and heat. The literature shows that CHP can significantly improve energy efficiency. The energy efficiency of CHP systems can reach 80%, compared to 30-40% for conventional systems. In addition, CHP can produce lower greenhouse gas emissions compared to traditional systems. The study also shows that CHP can be an economical solution to generate electrical energy from livestock manure. CHP systems can generate significant economic benefits in the long run.